How Communities Manage Risks of Crime and Violence - Petesch, Patti (World Bank, Washington, DC, 2013)
This report discusses principal causes and patterns of crime and violence; explains three theories of violence based on ideas, behaviors, and social interactions; and focuses on what distinguishes the communities that are more resilient to violence. Violence patterns have strong geographic, gender, and generational dimensions. Rates of crime and violence are usually higher in cities than rural areas, and within cities violence frequently clusters in poorer communities. While young men are the chief perpetrators and victims of crime and violence, problems of domestic violence against women continue to be severe in many localities around the world. Five broad areas of good practices may help communities struggling with crime and violence: (1) Provide crime and violence monitoring systems; (2) Advance policy frameworks to reduce societal fragility and social group inequalities; (3) Strengthen local institutional capacities to provide law and order and mediate disputes; (4) Prioritize local men's and women's economic opportunities; and (5) Require timely redress mechanisms for community development interventions.